Seismicity Associated With the Formation of a New Island in the Southern Red Sea - Eyles, Jade H. W.; Illsley-Kemp, Finnigan; Keir, Derek; Ruch, Joël; Jónsson, Sigurjón (Frontiers in Earth Science, 2018)
Volcanic eruptions at mid-ocean ridges are rarely witnessed due to their inaccessibility, and are therefore poorly understood. Shallow waters in the Red Sea allow the study of ocean ridge related volcanism observed close to sea level. On the 18th December 2011, Yemeni fishermen witnessed a volcanic eruption in the southern Red Sea that led to the formation of Sholan Island. Previous research efforts to constrain the dynamics of the intrusion and subsequent eruption relied primarily on GPS and InSAR methods, data for which was relatively sparse. Our study integrates InSAR analysis with seismic data from Eritrea, Yemen and Saudi Arabia to provide additional insights into the transport of magma in the crust that fed the eruption. Twenty-three earthquakes of magnitude 2.1 to 3.9 were located using the Oct-tree sampling algorithm. The earthquakes propagated southeastward from north of Sholan Island, mainly between December 12th and December 13th. The seismicity is interpreted as being induced by emplacement of a ~12 km-long dike. Earthquake focal mechanisms are primarily normal faulting and suggest the seismicity was caused through a combination of dike propagation and inflation. We combine these observations with new deformation modeling to constrain the location and orientation of the dike. The best-fit dike orientation that satisfies both geodetic and seismic data is NNW-SSE, parallel to the overall strike of the Red Sea. Further, the timing of the seismicity suggests the volcanic activity began as a submarine eruption on the 13th December. The new intrusion and eruption along the ridge suggests seafloor spreading is active in this region.